Accounting and Auditing : Ukraine - World Bank (Washington, DC, 2017)
This assessment of accounting and auditing practices in Ukraine is part of a joint initiative of the World Bank and International Monetary Fund (IMF) to prepare Reports on the Observance of Standards and Codes (ROSC). The assessment focuses on the strengths and weaknesses of the accounting and auditing environment that influence the quality of corporate financial reporting and includes both a review of both mandatory requirements and actual practice. The report uses International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA) as benchmarks and draws on international experience and good practice in the field of accounting and auditing regulation. All the key economic sectors in Ukraine rely on high quality financial information, which requires high quality private sector accounting and auditing. As Ukraine moves towards further reforms, liberalization and deregulation in efforts to foster an investment-friendly business environment enhanced financial transparency and improved accounting and auditing practices must support this. In this context, this report sets out policy recommendations to enhance the quality of corporate financial reporting and foster a financial reporting platform conducive to sustainable private and financial sector growth, thus increasing access to global financial markets and other tools of the market economy.